2022
DOI: 10.3389/feduc.2022.897473
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Opportunities to Learn on Peruvian Students’ Science Achievement in Program for International Student Assessment 2015

Abstract: Opportunities to learn (OTL) are considered important variables to enable equitable educational standards in teaching. The main objective of this work was to test a five-level hierarchical model to explain the general achievement and science competencies of Peruvian students in the Program for International Student Assessment (PISA) 2015, controlling for the student’s age and gender, and the economic, social, and cultural status, both for the student (ESCS) and the school (MESCS). The Peru database was taken f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
1
3
0
2
Order By: Relevance
“…Estos hallazgos ponen de relevancia la importancia de fortalecer los procesos y resultados de aprendizaje de competencias matemáticas y de lectura en el Perú, dado que estas son dos competencias importantes para el desarrollo de otras competencias, como las científicas, las tecnológicas y, en este caso, las competencias financieras. Si bien Saavedra y Gutiérrez (2020) resaltan las reformas y avances en la mejora del sistema educativo peruano en los dos últimos lustros, los resultados en evaluaciones internacionales a gran escala aún reflejan bajos niveles de desempeño (Bazán-Ramírez et al, 2022;Muelle, 2019).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estos hallazgos ponen de relevancia la importancia de fortalecer los procesos y resultados de aprendizaje de competencias matemáticas y de lectura en el Perú, dado que estas son dos competencias importantes para el desarrollo de otras competencias, como las científicas, las tecnológicas y, en este caso, las competencias financieras. Si bien Saavedra y Gutiérrez (2020) resaltan las reformas y avances en la mejora del sistema educativo peruano en los dos últimos lustros, los resultados en evaluaciones internacionales a gran escala aún reflejan bajos niveles de desempeño (Bazán-Ramírez et al, 2022;Muelle, 2019).…”
Section: Discussionunclassified
“…Asimismo, estudios realizados con diversos resultados de logro de estudiantes peruanos en PISA han mostrado reiteradamente el efecto del nivel socioeconómico y cultural (ESCS) de las familias de origen y de la escuela; por ejemplo, en lectura (Cueto, León, Muñoz, et al, 2016), en ciencias (Bazán-Ramírez et al, 2022) y en matemáticas, lectura y ciencias (Muelle, 2019). Asimismo, Murillo y Carrillo (2021) han reportado el efecto de variables socioeconómicas y de origen sobre el desempeño de estudiantes peruanos de secundaria en evaluaciones a gran escala en varias disciplinas.…”
Section: Discussionunclassified
“…For example, in a quasi-experimental study with 456 students from 23 schools, it was found that the reading achievement of students in classes where adaptive instruction was implemented was higher than that of students in classes where traditional methods were preferred (Houtveen et al, 1999). Other studies on this subject also indicated that there were significant relationships between adaptive instruction methods and students' achievement in reading (Bozkurt, 2022;Karaman, 2020) and in other areas (Bazán-Ramírez, 2022;Forbes et al, 2020). Research also suggested that such an approach can produce beneficial outcomes in terms of students' affective and psychological attributes like motivation and academic self-concept (Erdoğdu, 2020;Lau & Ho, 2020).…”
Section: Adaptive Instruction and Reading Achievementmentioning
confidence: 99%
“…Extant literature suggested a significantly positive impact of OTL on student achievement [27]. It was evidenced that middle school students were more likely to be well-supported in science learning and achieved better science performance in assessments when given more OTL [14]. Currently, OTL research revolves around STEM subjects, because researchers hold the belief that these disciplines which placed a strong emphasis on critical thinking and creativity merited additional OTL to enhance student learning results [28].…”
Section: Otlmentioning
confidence: 99%
“…Secondary analysis using PISA data across variables might reveal the correlations that were not reported in the descriptive statistics of PISA report [12]. Previous secondary analysis using PISA has provided robust positive connections between OTL and adolescents' mathematics and science performance [13,14], and more relationships are to be tested specifically in other subjects, such as digital reading [15]. Since the main subject of the latest round of PISA, i.e., PISA 2018, focused on digital reading, its background questionnaire involved reading provided valuable information on reading-specific OTL and its influencing factors.…”
Section: Introductionmentioning
confidence: 99%